2019
DOI: 10.1503/cjs.001617
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the patellofemoral joint in total knee arthroplasty

Abstract: Understanding the patellofemoral joint in total knee arthroplasty P atellofemoral complications historically have contributed up to 50% of revision surgery. 1 With modern design refinements and improved techniques, the burden of revision from patellofemoral complications is less than it was previously; however, these complications remain some of the most challenging problems in knee arthroplasty. Complications involving the patellofemoral joint (PFJ) can occur with both resurfaced and nonresurfaced patellae. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 54 publications
4
44
0
1
Order By: Relevance
“…Therefore, our study covers the clinically most relevant TKR type. Our data indicate that the thickness of the analyzed dome-shaped patellar component affects PF contact forces, patellar tilt, and patellar rotation which has also been reported by other research groups [6,8,43]. In this regard, it was found that a higher retropatellar loading due to an increase in the thickness of the patellar component might contribute to anterior knee pain after TKR [6,44].…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Therefore, our study covers the clinically most relevant TKR type. Our data indicate that the thickness of the analyzed dome-shaped patellar component affects PF contact forces, patellar tilt, and patellar rotation which has also been reported by other research groups [6,8,43]. In this regard, it was found that a higher retropatellar loading due to an increase in the thickness of the patellar component might contribute to anterior knee pain after TKR [6,44].…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, the difference in patellar component designs and the size of the patellar component are factors that influence the PF dynamics [28,37,38]. Regarding patellar resurfacing, the all polyethylene dome-shaped patellar component is currently the most common used design [8,28]. Therefore, our study covers the clinically most relevant TKR type.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations